2023
DOI: 10.1038/s41522-023-00383-7
|View full text |Cite
|
Sign up to set email alerts
|

Ecological change of the gut microbiota during pregnancy and progression to dyslipidemia

Abstract: The composition of the gut microbiome was previously found to be associated with clinical responses to dyslipidemia, but there is limited consensus on the dynamic change of the gut microbiota during pregnancy and the specific microbiome characteristics linked to dyslipidemia in pregnant women. We collected fecal samples from 513 pregnant women at multiple time points during pregnancy in a prospective cohort. Taxonomic composition and functional annotations were determined by 16S rRNA amplicon sequencing and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Some could facilitate a remodeling of the maternal intestine or influence digestive physiology during pregnancy. Many were associated with lipid metabolism, glycolysis and gluconeogenic metabolic pathways, which are important for maternal health [ 110 , 111 ]. Even without bacterial translocation, the release and transfer of soluble factors from bacteria into circulation, including short-chain fatty acids and serotonergic metabolites, have been found to be associated with gestational hypertension and diabetes [ 112 , 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some could facilitate a remodeling of the maternal intestine or influence digestive physiology during pregnancy. Many were associated with lipid metabolism, glycolysis and gluconeogenic metabolic pathways, which are important for maternal health [ 110 , 111 ]. Even without bacterial translocation, the release and transfer of soluble factors from bacteria into circulation, including short-chain fatty acids and serotonergic metabolites, have been found to be associated with gestational hypertension and diabetes [ 112 , 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesized that in the case of controlling for dietary precursors, the urinary TMA levels could reflect the composition and abundance of the gut microbiota, while the ratio of TMAO to TMA could indicate the FMO activity . Specifically, the study by Yang et al observed that the gut microbiota underwent significant alterations throughout pregnancy . The late pregnancy was accompanied by a decrease in microbial diversity, and alterations in the microbiota due to environmental factors may be pathogenic .…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of Proteobacteria and Enterobacteriaceae reflects host energy imbalance and an unstable microbial community (dysbiosis) ( Shin et al, 2015 ; Litvak et al, 2017 ). A study on maternal dyslipidemia during pregnancy found that clustering analysis of the intestinal microbiota, with dominant genera including Faecalibacterium , Blautia , and Bacteroides , showed higher levels of total cholesterol and triglycerides ( Yang et al, 2023 ). These high-abundance genera were similar to that of cluster 1 and cluster 2 in this study, both of which were the most common community compositions among the late pregnancy population.…”
Section: Discussionmentioning
confidence: 99%